HUBUNGAN ANTARA PENERIMAAN DIRI DENGAN PENYESUAIAN DIRI PADA WANITA BERCADAR - Muh Mustagfirin; Ruseno Arjanggi (Proyeksi: Jurnal Psikologi, 2020)
Every Muslim woman has the right to get the right and freedom to wear clothes that are in accordance with the guidelines of Islamic law and do not conflict with the norms and values that apply in society and culture in Indonesia. In Indonesia, the veil is still considered a taboo subject and has generated a lot of debate, the pros and cons regarding the use of veils among the people are still associated with Arabic culture, political elements, extremist groups and radical groups. This study aims to determine the correlation between self-acceptance and self-adjument in veiled women. The subject in this study were veiled muslim women in semarang, totaling 120 people. The sampling technique uses snowball sampling technique. Data collection uses a scale of adjustment with a discrimination index of 0,305-0,597 and α: 0,884. the self-acceptance scale with item discrimination index moved between 0,284-0,610 and α: 0,907. Analysis of the data in this st[udy used the Product Moment technique. Based on the result of statistical analysis  rxy: 0,776 with a significance level of p= 0,000 (p<0,01). The results of this study indicate that there is a positive relathionship between self-acceptance and self-adjusment in veiled women in semarang.